Investigating Turnover Intention: The Role Of Counterproductive Work Behavior And Job Stress - Valensiana, Brigita Febi; Khrisna Sawitri, Dewi (Dinasti Publisher, 2024)
This study aims to analyze the effect of job stress on turnover intention with counterproductive work behavior as a mediating variable among employees of Food Company in Sidoarjo. Data were collected from 97 permanent employees through a questionnaire. The analysis method used is Partial Least Square (PLS) to test the relationships between variables. The results show that job stress has a significant positive effect on turnover intention. Additionally, counterproductive work behavior is found to mediate the relationship between job stress and turnover intention. These findings indicate that increased job stress not only directly raises employees' intentions to leave the company but also enhances counterproductive behavior, which ultimately strengthens turnover intention. This research provides implications for company management in developing strategies to reduce job stress and counterproductive behavior to lower employee turnover rates.